The Struggles for Life of The Main Characters on A Man Called Otto(2022) Movie : An Individual Psychological Approach - Ar Rayyani, Rahmaanditya Finaurrum; Nugroho, Abdillah (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study explores the emotional and psychological journey of Otto Anderson, the main character in the 2022 film A Man Called Otto, through Alfred Adler’s Individual Psychology framework. The film portrays Otto as a grieving widower who undergoes a significant psychological transformation after the loss of his beloved wife. Employing a qualitative method and textual analysis, this research identifies five major Adlerian concepts in Otto’s character: inferiority complex, striving for superiority, lifestyle, creative self, and social interest. The findings reveal how Otto’s rigid behavior, emotional withdrawal, and repeated suicide attempts reflect a deep-seated inferiority complex and unresolved trauma. However, through interactions with new neighbors and acts of communal care, Otto gradually redirects his despair into purpose-driven actions, thus activating his creative self and developing a renewed sense of social belonging. This study not only contributes to character analysis using Adlerian psychology but also highlights the role of film as a reflective medium for mental health discourse, especially in portraying grief, resilience, and social reintegration.